Variability of sporadic-e (es) layer at two equatorial stations: fortaleza (3os, 38ow) and Ilorin (8.5on, 4.5oe) (2014)
The day time variability of sporadic-E (Es) layer at Fortaleza (3oS, 38oW) and Ilorin (8.5oN, 4.5oE) during the solstice and equinox periods have been investigated using hourly daily Digisonde ionograms. The result show that during the equinox period, the critical frequency (foEs) of the Es-layer at Fortaleza dropped to minimum values before rising to its first peack values by 0900 hrs LT and 1000 hrs LT in March and September respectively. On the other hand, a continuous rise in the value offEs from sunrise till the first peack values of 6.0MHz by 0800 hrs LT and 5.5MHz by 0700 hrs LT was observed during the June and December solstices respectively. At Ilorin, the fEs reached its first peack values of 5.5MHz by 1200 hrs LT and 6.0MHz by 1000 hrs LT during the March and September equinoxes respectively. A double peack of about 5.4MHz by 0800 hrs LT and 6.5MHz by 1300 hrs LT was observed during the June Solstice as compared to the single peack of about 7.00MHz during the December solstice. The height (hmEs) of Es was lower at Fortaleza than at Ilorin for all the seasons (with a difference of between 2 and 4 km, depending on the month). For all the seasons and months investigated, the E-layer was never observed earlier than 0900 hrs LT at Fortaleza. At Ilorin, the E-layer was formed right from sun rise with frequencies lower than at Fortaleza. These results comfirm the latitudinal variation of the sporadic-E layer at the equatorial region. It also showed that the E-layer is formed earlier in Ilorin than at Fortaleza with a time lag of about 3 hours.